Ispol'zovanie istochnikov informatsii v deyatel'nosti trenerov po boksu - Filippov, S. S.; Taymazov, V. A.; Kvachadze, D. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The questionaring of boxing coaches from St.-Petersburg (n=48) and Georgia (n=27) had allowed to reveal the main sources of information for coaches. The most popular sources are the athletes' diaries and the coaches' diaries, methodical materials, journals and books. It had been concluded that methodical materials are to be included in the informational systems and that journal and books are not accessible for boxing coaches.